EFEKTIVITAS INSTAGRAM SEBAGAI MEDIA PROMOSI DESA WISATA MALASARI, KECAMATAN NANGGUNG, KABUPATEN BOGOR The Effectiveness of Instagram as a Promotion Media of Malasari Tourism Village, Nanggung, Bogor District - Fitri Ardianti (Departemen Sains Komunikasi dan Pengembangan Masyarakat, Fakultas Ekologi Manusia, IPB, 2020)
ABSTRACTAccording to UU No. 10 2009, a tourist village is a tourist destination which integrates attractions, tourism facilities, accessibility, that are presented in a community-based living structures along with applicable procedures and traditions. To development a tourist village, it requires promotion activities to introduce products / services to consumers widely, one of which is using the social media, Instagram. The objectives of this research is to describe the effectiveness of Instagram as a promotional medium for the Malasari Tourism Village, to analyze the relationship between individual characteristics along the media exposure and the effectiveness of Instagram, as well as to analyze the effectiveness of Instagram actions after visiting Malasari Tourism Village. Quantitative data is processed using a correlation test with the selection of 52 respondents using Slovin techniques. The result of this research is that there is a relationship between individual characteristics of age along with Instagram media exposure with the effectiveness of Instagram as a Promotional tool, and there is a relationship of (attraction, comprehension) with returning to visit, and last there is a relationship between (attraction, comprehension, self-involvementac, and persuasion) with giving recommendations to others. Keywords: tourist village, institution effectiveness, after-visit action ABSTRAKMenurut UU No. 10 Tahun 2009 desa wisata merupakan suatu daerah tujuan wisata yang mengintegrasikan daya tarik wisata, fasilitas pariwisata, aksesibilitas, yang disajikan dalam suatu struktur kehidupan masyarakat yang menyatu dengan tata cara dan tradisi yang berlaku. Pengembangan desa wisata, perlu dilakukan kegiatan promosi untuk memperkenalkan produk/jasa kepada konsumen secara luas, salah satunya menggunakan media sosial instagram. Tujuan penelitian ini adalah, mendeskripsikan efektivitas instagram sebagai media promosi Desa Wisata Malasari, menganalisis hubungan karakteristik pengunjung dan keterdedahan media dengan efektivitas instagram, serta menganalisis hubungan efektivitas instagram tindakan setelah berkunjung pengunjung ke Desa Wisata Malasari.. Data kuantitatif diolah menggunakan uji hubungan dengan pemilihan 52 responden yang menggunakan teknik Slovin. Hasil dari penelitian ini adalah, terdapat hubungan antara karakteristik individu pada indikator usia dan keterdedahan media instagram dengan efektivitas instagram dan terdapat hubungan antara (daya tarik, pemahaman) dengan minat berkunjung kembali, serta terdapat hubungan antara (daya tarik, pemahaman, keterlibatan diri, dan persuasi) dengan rekomendasi kepada orang lain. Kata kunci: desa wisata, efektivitas instgram, tindakan setelah berkunjung